Turkish and Turkish Language and Literature Teachers' Views' on the Reading Skills and Turkey's Performance in PISA: A Focus Group Interview - Derya YILDIZ (Anı Publishing, 2021)
This study aims to examine Turkish and Turkish language and literature teachers' views on reading skills and Turkey's performance in PISA. A focus group interview, one of the qualitative research methods, was used in this study. Teachers' views on reading skills in PISA, the general situation in Turkey's PISA, the concept of the text, questions of measuring high-level skills and solutions were investigated by qualitative data analysis methods. The study group of the research consisted of teachers determined using criterion sampling technique, one of the purposeful sampling methods. The steps of the focus group interview were used in collecting the data, and content analysis techniques were used in the analysis. As a result of the research, teachers' opinions on reading skills in PISA; with incomplete information and low success themes; text concept; with texts in books and themes of changing text concept; questions measuring high-level skills; with ready-made questions and systematic questions themes; solutions are explained under the theme of continuous training.